Comparativo entre modelos de pórticos e contraventamentos de estruturas metálicas - Santos, Bruno Soares dos (2019)
In the Brazilian civil industry, reinforced concrete constructions have given way to metallic structures due to their efficiency and speed of assembly. However, in the design stage, the literature lacks data to indicate the most efficient model to choose. The objective of this work is to analyze a steel structure shed, using different models of frames and bracing as variables, using the computational method through the Rfem structural calculation program. The simulations showed that the heavier structures obtained better structural efficiency.